UNDERSTANDING CERTAIN ASPECTS OF MILITARY STRATEGY - Oyuntsetseg Densmaa; Baasankhuu Suren (International Journal of Innovative Technologies in Social Science, 2024)
Strategy is the most sophisticated form of military art, encompassing the theory and practice of organizing a nation’s armed forces for war and managing large-scale military operations (known as strategic operations). Strategy is derived from and follows political policy, serving as a unified plan for all branches of the military. Military strategy involves diminishing an adversary’s physical capacity and willingness to fight, continuing this effort until one’s objectives are met. It occurs in both wartime and peacetime and may involve the use of force, either directly or indirectly, as a threat. Military strategy is typically divided into four components: ends (objectives), ways (courses of action), means (resources), and risk. The practice of military strategy is described alongside military power, which is enhanced by nine “principles of war”: objective, maneuver, surprise, mass, economy of force, offensive, security, simplicity, and unity of command. A general will likely employ combinations of military strategies, integrating them into a series of operations or campaigns. The term "strategy" originates from the ancient Greek "Strategos," meaning military leader. It is derived from the words "Stratos" (soldier, army) and "Ago" (management, leadership). The practice of military strategy involves the planning and execution of operations aimed at achieving specific objectives in warfare. Military power is bolstered by nine key principles of war: First of all, focus efforts on a clearly defined goal and position forces effectively to gain a tactical advantage. Also, strike the enemy unexpectedly to disrupt their plans and concentrate combat power at the decisive point to overwhelm the enemy. Furthermore, allocate resources efficiently to maximize effectiveness and take the initiative to seize and maintain the advantage. Next principles are the protection one’s own forces and information from enemy actions and ensure plans and orders are straightforward and clear. Finally, maintain a centralized command structure for coherent strategy execution. These principles guide military leaders in crafting strategies that effectively utilize available resources and achieve desired outcomes in conflict scenarios.